2011
DOI: 10.1103/physrevlett.107.095004
|View full text |Cite
|
Sign up to set email alerts
|

Generation of High-Density Electrons Based on Plasma Grating Induced Bragg Diffraction in Air

Abstract: Efficient nonlinear Bragg diffraction was observed as an intense infrared femtosecond pulse was focused on a plasma grating induced by interference between two ultraviolet femtosecond laser pulses in air. The preformed electrons inside the plasma grating were accelerated by subsequent intense infrared laser pulses, inducing further collisional ionization and significantly enhancing the local electron density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…In our experiments, 800-nm Ti:sapphire femtosecond laser pulses with pulse energy of ∼25 mJ were frequency tripled by using three β-barium borate (β-BBO) crystals to generate the third harmonic (TH) pulse at 267 nm of ∼2 mJ pulse energy [10]. The schematic of the experiment setup is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, 800-nm Ti:sapphire femtosecond laser pulses with pulse energy of ∼25 mJ were frequency tripled by using three β-barium borate (β-BBO) crystals to generate the third harmonic (TH) pulse at 267 nm of ∼2 mJ pulse energy [10]. The schematic of the experiment setup is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While under the scheme of IR+blue plasma grating, deeper damage was created in morphology compared with the case of infrared filament or blue grating. 14 Additionally, periodical surface structures were also observed after slightly damage by the coherent blue grating, similar phenomenon cannot be visible in (c) and (f) because of near-surface plasma induced cooling solidification. Under few shots damage, ionization happened on the surface of metallic materials.…”
mentioning
confidence: 82%
“…Then the plasma grating was probed by a delayed infrared beam (IR) which was injected at Bragg angle in order to produce more electrons, 14 this scheme produces relatively high density of plasma. Here we name it as "IR+blue plasma grating".…”
mentioning
confidence: 99%
“…It was found that two noncollinearly overlapped filaments created a wavelengthscale periodic plasma density modulation [17][18][19], which guided the input pulses similar to a photonic crystal plasma waveguide. The incident pulses were partly guided along those waveguides [17], which is consistent with the observed filament profiles in the far-field region.…”
Section: Introductionmentioning
confidence: 99%